20. PERBEDAAN JUMLAH LEUKOSIT SETELAH TRANSPLANTASI KULIT SECARA AUTOGRAFT DAN ISOGRAFT PADA ANJING LOKAL (Canis lupus familiaris) Description of Leucocyte on Skin Transplantation Lessio by Autograph and Isograph on Local Canine (Canis Lupus familiaris) - Irnandha Rafdinal (Universitas Syiah Kuala, 2016)
This research aimed to determined the description of leucocyte on transplantation wound by autograph and isograph on local canine. This research used 4 local dogs. Sample animals were fasted 6 hours before surgery, then injected with atropine sulfate subcutaneously as premedication, followed by anaesthesized by ketamine and xylazine intramuscularly. The incision 3x3 cm was made on right chest’s skin and right side of thigh, then transplantation was carried out by autograft and isograph. Blood colection was conducted through chepalica vein for 1 ml on 0,3,6,9, and 12 day after treatment. Data were analyzed using split plot pattern ANOVA. The results showed that the total of leucocyte after skin transplantation by autograph on day 0, 3, 6, 9, and 12 were (7.80±0.57) x 103/mm3, (12.36±0.06) x 103/mm3, (12.98±0.32) x 103/mm3, (15.42 ± 0.11) x 103/mm3, and (17.66±0.45) x 103/mm3, and total of leucocyte after skin transplantation by isograph on day 0, 3, 6, 9, and 12 were (6.80±0.57) x 103/mm3, (9.35±0.36) x 103/mm3, (12.59±4.17) x 103/mm3, (16.11± 1.10) x 103/mm3, and (18.57±0.33) x 103/mm3. Based on the result it can be concluded that total of leucocyte on isograph skin transplantation is higher than autograph skin transplantation. ____________________________________________________________________________________________________________________ Key words: leucocyte, autograph, isograph